2010
DOI: 10.1159/000289353
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Lobar and Non-Lobar Spontaneous Intracerebral Haemorrhage in a Predominantly Hispanic-Mestizo Population – The PISCIS Stroke Project: A Community-Based Prospective Study in Iquique, Chile

Abstract: Background: The incidence of intracerebral haemorrhage (ICH) in Hispanics is high, especially of non-lobar ICH. Our aim was to ascertain prospectively the incidence of first-ever spontaneous ICH (SICH) stratified by localisation in a Hispanic-Mestizo population of the north of Chile. Methods: Between July 2000 and June 2002 all possible cases of ICH were ascertained from multiple overlapping sources. The cases were allocated according to localisation. Those with vascular malformations or non-identifiable local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 84 publications
3
12
0
Order By: Relevance
“…Although studies of patients with ICH with prior use of antiplatelet agents are less consistent,22–26 most have shown a positive relationship with haematoma growth 23–26. Epidemiological data have also shown that ICH related both to antiplatelets and anticoagulants are more likely to be lobar 27. While our analysis is limited by the small number of patients treated with antithrombotics, the results support the hypothesis generated from observational studies that prior use of antithrombotic therapy increases the risks of greater haemorrhage in acute ICH.…”
Section: Discussionsupporting
confidence: 76%
“…Although studies of patients with ICH with prior use of antiplatelet agents are less consistent,22–26 most have shown a positive relationship with haematoma growth 23–26. Epidemiological data have also shown that ICH related both to antiplatelets and anticoagulants are more likely to be lobar 27. While our analysis is limited by the small number of patients treated with antithrombotics, the results support the hypothesis generated from observational studies that prior use of antithrombotic therapy increases the risks of greater haemorrhage in acute ICH.…”
Section: Discussionsupporting
confidence: 76%
“…Prior studies suggested the risk for intracerebral haemorrhage (ICH) to be marginally greater in men than in women. This differential risk by sex might be driven by an excess of deep haemorrhage in men, [44, 45] although it is well know that the risk of subarachnoid haemorrhage (about 5% of all HS) is much greater in women than in men. HS incidence rates are reportedly slightly higher in Eastern Asia, where ICH has historically accounted for a larger percentage of all strokes than in Western populations possibly due to the increased prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to take account of three potential confounding factors that should be described, and preferably controlled or adjusted for in comparisons of cases and controls: first, patient age, given the increasing CAA prevalence with age9; second, cognitive impairment (and its severity), given the greater prevalence of CAA in those with cognitive impairment than in those without dementia9 15; and third, patients' racial origins, given racial differences in the prevalence of apolipoprotein E polymorphisms which have been associated with ICH due to CAA16 17 and racial differences in the proportion of ICH in a lobar location 18…”
Section: Introductionmentioning
confidence: 99%